Pengaruh Social Media Marketing Tiktok dan Online Consumer Review terhadap Keputusan Pembelian Produk Skintific - Nabilah , Agne; Wardhana, Aditya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Technology is becoming an increasingly important part of everyone's life because of its rapid development. Indonesians are currently feeling the benefits of technological advancements, including digitizing entertainment media and creating content (TikTok) which is increasingly popular. In addition, Tiktok offers a Tiktok for business feature called Tiktok Shop. This feature can help businesses expand their market by encouraging creativity in a study conducted to evaluate the potential influence of TikTok's social media marketing and online consumer reviews on purchasing decisions for Skintific-branded products. The focus of this study is quantitative, using descriptive and associative causal research methods. Data was collected through a Google Form questionnaire sent to 96 women between the ages of 15 and 35, all of whom were users of Skintific products and the TikTok app. The sampling method used is non-probabilistic, more specifically intentional sampling. Data analysis was carried out using multiple linear regression, using SPSS version 25 to process the collected data. The results showed that TikTok social media marketing variables and online consumer reviews had a positive and significant influence on the purchase decision of Skintific products, both partially and simultaneously. According to the conclusion drawn from the coefficient of determination, it was established that 52.1% of purchasing decisions for Skintific products are due to the influence of TikTok's social media marketing and online consumer reviews. The remaining 47.9% indicated that other variables not examined in the study also had an impact on purchasing decisions